Mendedah Kalimat Bahasa Arab Perspektif Teori Sintaksis Struktural - Insanul Hasan (Diwan: Jurnal Bahasa dan Sastra Arab, 2019)
This study applies a syntactic approach in the modern linguistic literature on Arabic lingual data. In the perspective of contemporary linguistic schools, the application of syntactic studies to Arabic is rarely done by reviewers. The complexity of the grammatical structure of Arabic is one of the important reasons. Through this study, the author wants to break this assumption. A structural syntactic approach can be applied to examine the Arabic sentences as well as in other languages. Structural analysis that emphasizes the analysis of direct constituents can still be applied to Arabic which has many specific characteristics. Using an analytical model introduced by Bloomfield, Harris, and Hocket, direct constituent analysis is proven to be applicable to Arabic.